Evaluate the Protective Effect of Bromelain against Scopolamine-Induced Histological Lesions in the Brain Tissues of Albino Rats - Ahmed, Tabarek Abd-Alrhman; Abdulla, Buthina A. (American Journal of Biology and Natural Sciences, 2025)
The present study aimed to evaluate the protective effect of bromelain against scopolamine-induced histological lesions in the brain tissues of albino rats. For the study, 25 adult female rats were used, which were purchased from the animal house at the Veterinary Medicine College of Tikrit University. Between 10 and 12 weeks of age, the animals weighed an average of 207 grams, with a range of 181 to 204 grams. The experiment was carried out at the animal home of the College of Veterinary Medicine at Tikrit University between August 29, 2024, and September 11, 2024. the results showed in Scopolamine group, the cortex of brain had containing great cavities with diffused Internal pyramidal cells which were surrounded by vacuolar degeneration around its nuclei. the fine micro-blood vessels or capillaries were surrounded by WBCs. in the third group, the internal pyramidal cell layer was enriched with medium sized and small sized of neurons, few glial cell were demonstrated among the pyramidal cell, micro-blood capillaries were detected in the cortex. in the fourth group, the brain cortex was surrounded by pial membrane of meninges with presence of meningeal blood vessels at the periphery of cortex. the molecular layer was outer most which was formed by few small pyramidal cell surrounded by fine foamy nerve facicle, the external granular layer was containing small medium sized pyramidal cells. in fifth group, the brain cortex was surrounded by meningeal arteries which had blood clot and thick wall, the molecular layer had few pyramidal cell, surrounded with foamy appearance of nerve bundle. It is concluding the effective role of bromelain in improving brain tissue, as it reduces tissue lesions and lymphocyte infiltration caused by scopolamine.